Molecular Dissection of DAAM Function during Axon Growth in Drosophila Embryonic Neurons. - Földi, I.; Tóth, K.; Gombos, R.; Gaszler, P.; Görög, P.; Zygouras, I.; Bugyi, B.; Mihály, J. (Cells, 2022)
Axonal growth is mediated by coordinated changes of the actin and microtubule (MT) cytoskeleton. Ample evidence suggests that members of the formin protein family are involved in the coordination of these cytoskeletal rearrangements, but the molecular mechanisms of the formin-dependent actin-microtubule crosstalk remains largely elusive. Of the six Drosophila formins, DAAM was shown to play a pivotal role during axonal growth in all stages of nervous system development, while FRL was implicated in axonal development in the adult brain. Here, we aimed to investigate the potentially redundant function of these two formins, and we attempted to clarify which molecular activities are important for axonal growth. We used a combination of genetic analyses, cellular assays and biochemical approaches to demonstrate that the actin-processing activity of DAAM is indispensable for axonal growth in every developmental condition. In addition, we identified a novel MT-binding motif within the FH2 domain of DAAM, which is required for proper growth and guidance of the mushroom body axons, while being dispensable during embryonic axon development. Together, these data suggest that DAAM is the predominant formin during axonal growth in Drosophila, and highlight the contribution of multiple formin-mediated mechanisms in cytoskeleton coordination during axonal growth.